2015
DOI: 10.1021/es506316t
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring the Spatial and Historical Variations of Persistent Organic Pollutants (POPs) in an Industrial Region

Abstract: Several persistent organic pollutants (POPs) like polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), polychlorinated naphthalenes (PCNs), and polybrominated diphenyl ethers (PBDEs) were measured in needle, branch, bark, and tree ring samples in pine samples collected at 27 sites (21 industrial, 6 background) in Aliaga industrial region in Turkey. Soil, litter, and air samples were also collected to investigate the relationships between the air and soil, litter, and tree components. Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(41 citation statements)
references
References 48 publications
6
33
1
1
Order By: Relevance
“…It can be concluded that PCB levels were not very different in 2012 from 2003 to 2004. This is further supported by a recent study investigating the historical variations of POPs using dated tree cores at 14 industrial and background sites in Izmir region (Odabasi et al 2015) showing that PAH and PCB concentrations in tree ring samples (that are suggested to be representative of ambient air levels) were stable or slightly increasing during the period of 2001-2011. Therefore, the estimated risk levels associated with inhalation and dermal contact in this study for both PAHs and PCBs are probably reasonable estimates for the current levels, assuming the same values for the other variables (inhalation rate and body weight) in the exposure-risk model.…”
Section: Exposure and Risk Assessmentsupporting
confidence: 66%
“…It can be concluded that PCB levels were not very different in 2012 from 2003 to 2004. This is further supported by a recent study investigating the historical variations of POPs using dated tree cores at 14 industrial and background sites in Izmir region (Odabasi et al 2015) showing that PAH and PCB concentrations in tree ring samples (that are suggested to be representative of ambient air levels) were stable or slightly increasing during the period of 2001-2011. Therefore, the estimated risk levels associated with inhalation and dermal contact in this study for both PAHs and PCBs are probably reasonable estimates for the current levels, assuming the same values for the other variables (inhalation rate and body weight) in the exposure-risk model.…”
Section: Exposure and Risk Assessmentsupporting
confidence: 66%
“…Surprisingly, PBDEs were also present in tree-ring sections which represent 1900s, quite long time before the 1970s when the commercial PBDE mixtures were first produced. This indicated that similar to PCBs and PCNs, combustion emissions are the sources of PBDEs in stem samples before the industrialization in the study area (Odabasi et al, 2015). Similarly, PBDEs unexpectedly presented in the components of raw sinter mix used in the iron ore sintering process, including iron ores (ca.…”
Section: Survival and Formation Of Pbdes In Combustion Systemmentioning
confidence: 78%
“…Although rice straw do contain PBDEs (934 ng kg -1 ) and PCDD/Fs (48.9 ng kg -1 ), the higher ratio of PBDEs to PCDD/Fs emission factors compared to rice straw contents indicate that formation of PBDEs occurred during rice straw burning, and not from the thermal release from their original content (Chang et al, 2014a). Odabasi et al (2015) measured PAHs, PCBs, PCNs and PBDEs in tree ring samples in pine samples collected at industrial and background sites in Turkey. Historical trends of all POP concentrations indicated an increase with time in industrial and background sites.…”
Section: Survival and Formation Of Pbdes In Combustion Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources of particle-phase PAHs were investigated using diagnostic plots and diagnostic ratios in Izmir urban area and it was indicated that traffic emissions (petroleum combustion) and residential heating were the dominant PAH sources (Demircioglu et al, 2011a). Other previous studies in Aliaga have also indicated that iron-steel plants, ship-breaking activities, petroleum refinery and petrochemical plant are significant POP emitters in the region (Cetin and Odabasi, 2007b;Odabasi et al, 2009;Odabasi et al, 2015). Therefore, higher PAH, PCB, and PBDE concentrations observed in the industrial site of the present study could be attributed to emissions from the industries located in the vicinity of the sampling site.…”
Section: Pop Concentrations In Atmospheric Particlesmentioning
confidence: 99%